Green Chemistry for Environmental Remediation. - Sanghi, Rashmi; Singh, Vandana (Hoboken : John Wiley & Sons, 2012)
The book presents an in depth review from eminent industry practitioners and researchers of the emerging green face of multidimensional environmental chemistry. Topics such as green chemistry in industry, green energy: solar photons to fuels, green nanotechnology and sustainability, and green chemistry modeling address a wide array of iusses encouraging the use of economical ecofriendly benign technologies, which not only improve the yield, but also illustrates the concept of zero waste, a subject of interest to both chemists and environmentalists alike.
5.3.2 Focused Group Discussions5.4 Students' Feedback; 5.4.1 Analyses of Open Comments from Students; 5.4.2 Interviews; 5.5 Conclusion; References; 6. Capability Development and Technology Transfer Essential for Economic Transformation; 6.1 Introduction; 6.2 The Importance of R & D; 6.2.1 Research and Development Expenditure; 6.3 Knowledge Creation and Technology Transfer; 6.3.1 Development of an RDT Voucher System; 6.3.2 External Engagement; 6.3.3 Organizational RDT Planning; 6.3.4 Structural Changes; 6.4 Technology Transfer Future; 6.5 Applications to Green Chemistry; 6.6 Conclusions.
Acknowledgements.
Includes bibliographical references and index.
Print version record.
Keywords: Green chemistry; Environmental chemistry -- Industrial applications; Environmental protection; Sustainable development; Chemical engineering; Engineering; Natural history; Science; Electronic books